The Influence of Viral Marketing and Online Customer Reviews on Consumer Buying Interest (Case Study on Gacoan Noodles) - Putrawan, Muh. Rizah; S., Ratnah (Cita konsultindo, 2026)
This study is expected to find out how Viral Promoting and Online Client Audits affect buyers' buying interest (Contextual analysis on Gacoan Noodles). This exploration was directed using the Different Straight Relapse examination tool in SPSS. The speculation uses a t-test with exploration results showing that viral showcases affect buyers' buying interest and online client surveys affect buyers' buying interest. The first speculation assumes that the viral display significantly affects buyers' buying interest for Mie Gacoan's focus products. The next speculation is that web-based client surveys significantly affect customer purchase interest towards the learning situation at Mie Gacoan.